Women's Representation In Parliament and its Impact On Gender Equality : an Analysis Of Women's Social Welfare, Health, Education, and Participation In The World Of Work - Muh Askal Basir; Berty Sadipun (Jurnal Mamangan, 2023)
The study aims to analyze the relationship between women's representation in parliament and gender equality, and its impact on social aspects such as health, education, and women's participation in the workforce. The research is motivated by gender inequality that still occurs, especially in developing countries, where the role of women in politics is believed to accelerate the achievement of gender equality, although their limitations in political decision-making still exist. The main focus of this study is the importance of women's representation in parliament in influencing more inclusive social policies. Using a quantitative approach and linear regression, this study explores the relationship between women's leadership in parliament and indicators of gender inequality, such as the Gender Inequality Index (GII), maternal health, women's participation in the workforce, and women's education in relevant countries. The results of the study indicate a significant positive relationship between women's representation in parliament and a decrease in gender inequality and an increase in social welfare, especially in terms of maternal health and women's participation in the workforce. This study fills the gap in research related to the direct relationship between women's political roles and socio-economic factors in the context of developing countries. The novelty of the study lies in its integrative approach that links women's political influence on health, economic and education sectors, and their impact on gender equality. In conclusion, increasing women's representation in parliament contributes significantly to reducing gender inequality and improving policies that support women, so that countries with high gender inequality can use countries with better gender equality as policy models